Sorghum as a monocot model for drought research - Fontanet-Manzaneque, Juan B.; Hernández, Daniela M.; Giordano, Andrea; Caño-Delgado, Ana I. (Frontiers in Plant Science, 2025)
Climate change is intensifying drought events, posing a major threat to global food security. Sorghum bicolor (L.) Moench (Sorghum), a C4 monocot grass, is emerging as a valuable model for drought research due to its natural tolerance to water limitation and adaptability to semi-arid and arid environments. Sorghum cultivation requires significantly less water than major cereals such as rice, maize, and wheat, making it an attractive crop for sustaining agricultural productivity under water-limiting conditions. In fact, Sorghum uses up to 34% less water than rice in rainfed systems and up to 50% less under irrigation, with rice-to-Sorghum substitution potentially reducing water demand by 33%. Its lower water requirements, along with the compact growth of commonly used accessions such as TX430 and BTx623, make Sorghum a practical system for experimentation, particularly in genome editing studies. Maize, which shares close genetic similarity and also belongs to the Panicoideae subfamily, could particularly benefit from Sorghum-based insights. Sorghum also overcomes key limitations of model species such as Arabidopsis thaliana, offering greater relevance to monocot crops. Additionally, advances in metabolomics, transcriptomics, proteomics, phenomics, population genomics and pangenomics are expanding our understanding of the molecular and physiological mechanisms underlying Sorghum’s drought resilience. Despite these advantages, challenges remain in transformation efficiency and the availability of genomic tools. This review highlights Sorghum’s drought tolerance mechanisms, available omics and genetic tools, described drought-related genes and regulatory networks, and the limitations and progress in gene manipulation for climate-resilient crop development. Sorghum uniquely combines the advantages of a staple crop and a model organism, making it a powerful next-generation system for climate-resilient agriculture.